BOTH ORAL PASSIFLORA INCARNATA AND OXAZEPAM CAN REDUCE PRE-OPERATIVE ANXIETY IN AMBULATORY SURGERY PATIENTS: A DOUBLE-BLIND, PLACEBO-CONTROLLED STUDY - Azimaraghi, Omid; Yousefshahi, Fardin; Khatavi, Fatimah; Zamani, Mohammad Mahdi; Movafegh, Ali (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Pre-operative anxiety control without increased post-operative psychomotor dysfunction is an anesthesia concern especially in ambulatory surgery; so, the development of a strong anxiolytic with minimal psychomotor impairment for premedication is desirable. In this study, it was hypothesized that Passiflora incarnata decreases pre-operative anxiety (PAN) similar to oxazepam. Methods: In this double-blinded placebo controlled study, 128 patients were randomized into Passiflora group (n=68) who received oral P. incarnata and oxazepam group (n=60) who received oxazepam (10 mg) as premedication, 90 minutes before surgery. A numerical rating scale (NRS) was used for each patient to assess anxiety before, and 90 minutes following premedication. Psychomotor function was assessed with the trigger dot test (TDT) and the digit-symbol substitution test at arrival in the operating room, and 90 minutes after tracheal extubation. Results: The 90th minutes NRS anxiety scores were significantly lower in the Passiflora group compared with oxazepam group (p<0.001). There were no significant differences in psychological variables, in groups, in the postanesthesia care unit. Conclusion: In outpatient surgery, administration of oral P. incarnata as a premedication reduces PAN with similar psychomotor function impairment compared with pre-operative oral oxazepam.